Islamic Philanthropic: The Generosity of the Muhammadiyah Residents of Medan City during the Covid-19 Pandemic - Irfan, Irfan; Hani, Syafrida; Amal, Bakhrul Khair (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the perceptions of Medan City Muhammadiyah residents about the economic burden of the community during the Covid-19 pandemic, as well as analyze the level of awareness of Medan City Muhammadiyah residents to pay zakat, infaq, alms and waqf to help the community's economic problems due to the Covid-19 pandemic. The survey design was conducted to collect data through a questionnaire (questionnaire) to 200 respondents who were analyzed using descriptive statistics. The results of the study found that the majority of Muhammadiyah residents agreed and had a high perception that the Covid-19 pandemic had caused an increase in the economic burden on the community during the Covid-19 pandemic. In addition, the majority of Muhammadiyah residents in Medan City have a very high level of awareness for tithing, infaq, charity and waqf in order to help the community's economic problems due to the Covid-19 pandemic.